Capital movements and their control : proceedings of the second Conference of the International Center for Monetary and Banking Studies - International Center for Monetary and Banking Studies; Swoboda, Alexander K. (Leiden : A. W. Sijthoff, 1976)
This book examines the direct effects of controls on capital movements. The Center's concern with the interaction of theory and practice which make up the part 11 of this volume
At head of title: Institut universitaire de hautes études internationales.
Includes bibliographical references and index.
usc 06/06/2018; 27/06/2018
Loans
Keywords: Capital movements